Inovasi Klepon Substitusi Tepung Mocaf (Modified Cassava Flour) dengan Perbedaan Konsentrasi Ekstrak Kulit Buah Naga (Hylocereus Polyrhizus) Ditinjau dari Mutu Sensori - Nur Azizah; Lilis Sulandari; Lucia Tri Pangesti; Aisyah Nurin Kamiliya (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of different concentrations of red dragon fruit peel extract on the sensory quality and nutritional content of klepon made from mocaf flour (Modified Cassava Flour) substitute. The study used an experimental method with three concentration treatments of red dragon fruit peel extract, namely 60%, 80%, and 100%. The sensory qualities observed included color, shape, texture, aroma, taste, and overall preference. Sensory tests were carried out by 35 panelists using a hedonic scale, then the data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's test at a significance level of 5%. The results showed that different concentrations of red dragon fruit peel extract significantly affected color, texture, aroma, taste, and overall preference (p<0.05), but did not significantly affect shape (p>0.05). The best treatment was obtained at an extract concentration of 80%, with a color score of 3.80, shape 3.40, texture 3.83, aroma 3.37, taste 4.09, and overall preference 4.09. Nutritional content analysis of the best treatment showed a total energy of 237.52–241.76 kcal/100 g, water content of 40.12–41.24%, carbohydrate content of 54.53–55.54%, protein content of 2.96–3.10%, fat content of 0.80–0.84%, and ash content of 0.43–0.44%. The results showed that substitution of mocaf flour with the addition of red dragon fruit peel extract has the potential to produce klepon with good sensory quality and nutritional value that supports the development of local food based on natural ingredients.